Comparing a new Gini test with other symmetry tests when median is known. Issue 8 (14th September 2019) - Auda, Hend; Niewiadomska–Bugaj, Magdalena
ABSTRACT: Wang et al. (2013 ) provided a comprehensive study of 14 tests, including two tests based on the Gini mean difference (GMD) introduced by Auda (2006), applicable for data from populations with an unknown median. This paper is a similar study of symmetry tests applicable for data from populations with a known median. We are showing that GMD tests compare favorably with several existing procedures in controlling the type I error as well as in power. Results of the study are shown graphically, which makes the tests' power easy to assess.